The ethics of professional accountants: an Aristotelian perspective. Issue 2 (20th February 2017) - West, Andrew
Abstract : Purpose: The purpose of this paper is to examine how Aristotle's ethics can be applied to the ethics of professional accountants (PAs), in relation to the approach adopted by the International Federation of Accountants (IFAC), and to consider the reasons that justify the Aristotelian approach. Design/methodology/approach: The paper outlines IFAC's approach and identifies several weaknesses. Three themes of Aristotle's Nicomachean Ethics are applied to the work of PAs. Reasons why this perspective is more suitable for PAs are then articulated. Findings: Several aspects of Aristotle's ethics can be fruitfully applied to the ethics of PAs. These include the relationship between function, goals and the good, an awareness of the human goal to achieve eudaimonia, the development of both excellences of character and of intelligence, and the significance of non-rational aspects of morality, including emotions, will, responsibility and choice. Research limitations/implications: This perspective provides an alternative conceptualisation of the ethics of PAs. Although it does not provide concrete guidance regarding what the ethical approach to specific situations may be, it presents a useful counterpoint to existing approaches that are largely deontological and utilitarian. Practical implications: This paper provides accountants in practice with a more comprehensive and adequate perspective on what it means for a PA to be ethical, and raises several issues related to how ethics is included in the education and training of accountants. Originality/value: Investigating the philosophical basis for professional ethics approaches professional codes of ethics in a way that it is not typically considered. The paper also provides a more comprehensive application of Aristotelian ethics than previous work.